PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN RESTORAN KAFE BETAWI DI JAKARTA - Muhammad Zainudin (2013)
This study was conducted to examine the effect of Service Quality and Customer Satisfaction Against Price In Restaurants Cafes Betawi in Jakarta. The population in this study a total of 100 students UPN "Veteran" Jakarta economics faculty workforce management department from 2009 to 2012. Data obtained from the questionnaires were distributed. Obtained a total sample of 100 people in the study. The analysis technique used is multiple linear regression and t-test using statistical hipotetsis and F-statistics with a confidence level of 5%. These results indicate that the quality of service and price have a significant effect on customer satisfaction. We suggest to the Betawi Kafe Restaurant Owner to pay attention to other factors that affect customer satisfaction. Variable Quality of Service in this study is the most influential variable on the Quality of Service is shown from the calculated value of t is greater than t-table and has a significance value of 6.898.